Fungsi Dewan Perwakilan Daerah dalam Perencanaan dan Pengawasan terhadap Pengelolaan Keuangan Negara (APBN) - Fazky Muhammad Hasa; Efik Yusdiansyah; Fabian Fadhly Jambak (Bandung Conference Series: Law Studies, 2022)
Abstract. The DPD has the authority to submit draft laws to the DPR, participate in discussing draft laws and provide considerations to the DPR on the APBN Bill. The word "participate" in the 1945 Constitution article 22D paragraph (2) discusses the draft bill that makes the DPD not have effective legislative power. The word "can" in Article 22D paragraph (1) makes the DPD not have effective power in terms of supervision over the implementation of the Act. DPD in Article 23 paragraph (2) of the phrase "taking into account the considerations of the DPD" makes the DPD not have effective power in terms of budget functions. Based on this phenomenon, the problems in this research are formulated as follows: (1) What are the functions, objectives and positions of the Regional Representatives Council in providing considerations and discussions on the RAPBN? (2) How is the external supervision carried out by the Regional Representatives Council on the implementation of the APBN? The approach method used in this research is normative juridical, namely legal research conducted by examining library materials or secondary data. The results of this study are: In giving consideration and discussion of the RAPBN function, purpose, and position of the DPD, the function of the DPD is considered to be still not balanced with the function of the DPR, the limited authority of the DPD shows the objectives of the Regional Representative Council. Regional Representative Council with limited supervision which is only regulated in the 1945 Constitution of the Republic of Indonesia. Abstrak. DPD memiliki kewenangan mengajukan rancangan undang-undang kepada DPR, ikut membahas rancangan undang-undang serta memberikan pertimbangan kepada DPR atas RUU APBN. Kata “ikut” dalam UUD 1945 pasal 22D ayat (2) membahas rancangan RUU membuat DPD tidak mempunyai kekuasaan legislatif yang efektif. Kata “dapat” dalam pasal 22D ayat (1) membuat DPD tidak mempunyai kekuasaan yang efektif dalam hal pengawasan atas pelaksaaan Undang-Undang. DPD dalam Pasal 23 ayat (2) adanya frase “dengan memperhatikan pertimbangan DPD” membuat DPD tidak mempunyai kekuasaan yang efektif dalam hal fungsi anggaran. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana fungsi, tujuan dan kedudukan Dewan Perwakilan Daerah dalam memberikan pertimbangan dan pembahasan atas RAPBN? (2) Bagaimana pengawasan eksternal yang dilakukan Dewan Perwakilan Daerah atas pelaksanaan APBN? Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis normatif, yaitu penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau data sekunder. Hasil dari penelitian ini adalah: Dalam memberikan pertimbangan dan pembahasan RAPBN fungsi, tujuan, dan kedudukan DPD ialah fungsi DPD dianggap masih belum seimbang dengan fungsi DPR, Kewenangan DPD yang terbatas menunjukkan tujuan dari Dewan Perwakilan Daerah. Dewan Perwakilan Daerah dengan melakukan pengawasan terbatas yang mana hanya diatur di dalam konstitusi Undang-undang Dasar 1945.